Environmental pollution liability insurance and green innovation of enterprises: Incentive tools or self-interest means? - Ning, Jinhui; Yuan, Zeming; Shi, Fang; Yin, Shi (Frontiers in Environmental Science, 2023)
The existing theoretical research on environmental liability insurance mainly focuses on system construction, development status and other aspects, and mainly consists of normative research, with relatively little empirical research. This paper uses empirical research methods to explore the impact of environmental liability insurance on the green innovation of enterprises and examines the driving role of environmental liability insurance in green innovation from the perspective of green governance. This paper, based on the list of enterprises purchasing environmental pollution liability insurance (EPLI) as published by the Ministry of Ecology and Environment, explores the impact of EPLI on the green innovation of enterprises. It is found that purchasing EPLI can significantly improve the green innovation of enterprises. The effect path test shows that EPLI can promote the green innovation of enterprises by relaxing financing constraints and reducing agency costs. The heterogeneity scenario test shows that compared with non-state-owned enterprises, non-heavily polluting enterprises, and enterprises in regions with a lower intensity of environmental regulation, EPLI plays a stronger role in the promotion of green innovation of state-owned enterprises, heavily polluting enterprises and enterprises in regions with a higher intensity of environmental regulation. In addition, it is found that the promotion effect of EPLI on green innovation is mainly reflected in the significant improvement of high-quality green innovation and the optimization of the structure of the green patent output. This paper affirms the positive role of EPLI on the green operations of enterprises and provides empirical evidence that green insurance serves the development of the green innovation of enterprises.